Emergency transportation for acute alcohol intoxication four years after the coronavirus disease 2019 pandemic: a retrospective observational study - Marina Minami; Natsuko Nakamura; Masamitsu Eitoku; Atsufumi Kawauchi; Takeshi Murakami; Narufumi Suganuma; Kingo Nishiyama; Masato Miyauchi (Komiyama Printing Co. Ltd, 2024)
Background: In a study conducted in Kochi Prefecture, Shikoku, Japan, during the early stages of the pandemic in spring 2020, we found that emergency transportations due to acute alcohol intoxication decreased. We aimed to determine how the decline in the number of emergency transportations due to acute alcohol intoxication changed during the four years following the COVID-19 pandemic's onset. Methods: This study used data of 107,013 emergency transportations from the Kochi-Iryo-Net database, Kochi Prefecture's emergency medical and wide-area disaster information system. We categorized emergency transportation cases according to the diagnoses entered into the system by the attending physician, which were then divided into alcohol- and non-alcohol-related intoxication cases based on the diagnostic codes in the International Classification of Diseases Manual, 10th edition, Clinical Modification. We performed chi-square tests and multiple logistic regression to examine the association between emergency transportations and acute alcohol intoxication. Results: The number of emergency transportations due to acute alcohol intoxication was 412 (1.8%) in 2019, and it declined to 268 (1.4%), 248 (1.2%), 270 (1.2%), and 283 (1.3%) in 2020, 2021, 2022, and 2023, respectively. After adjusting for confounding factors such as fire department and age, a significant decrease was observed in the subsequent years compared with 2019 (2020: adjusted odds ratio, 0.79; 95% confidence interval, 0.68-0.93; 2021: adjusted odds ratio, 0.74; 95% confidence interval, 0.63-0.87; 2022: adjusted odds ratio, 0.73; 95% confidence interval, 0.62-0.85; 2023: adjusted odds ratio, 0.76; 95% confidence interval, 0.65-0.89). Conclusions: This study examined changes in emergency transportation due to acute alcohol intoxication during and after the COVID-19 pandemic, especially when social events and other activities returned to "normal." Compared with 2021, which was when emergency transportations due to acute alcohol intoxication were at their lowest, a slight increase was observed in the number of transportations in subsequent years.